Pengaruh Motivasi Belajar Dan Perhatian Orang Tua Terhadap Kesiapan Belajar Peserta Didik - I Komang Sucandra (JURNAL INOVATIF ILMU PENDIDIKAN, 2021)
This research was motivated by the phenomenon that the learning readiness of the fifth grade students of public elementary schools in the Raden Intan cluster was low. The research aimed to determine the influence of learning motivation and parents’ attention on students’ learning readiness. In this research the writer used ex-post facto research. The population of this research consisted 132 students with a sample 56 students who was taken by using probability sampling techniques, namely proportionate stratified random sampling. The data collecting techniques used in this research were observation, interviews, and questionnaires. The data analysis used simple linear regression formula and multiple linear regression. The results showed a positive and significant influence of learning motivation and parents’ attention toward students’ learning readiness at the fifth grade of elementary school.